ANALISIS KEBUTUHAN BAHAN AJAR LEMBAR KERJA SISWA PELAJARAN MATEMATIKA BERBANTUAN ICT PADA TINGKAT SMA - Nadia Amalia; Citra Megiana Pertiwi; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The study aims to provide results from an analysis of the need for such materials as ICT at Senior High School levels. The method used in this study is a qualitative descriptive method, with data collected through Google form spread by the respondents of 5 math subjects from several Senior High Schools and 10 students at one Senior High School in Sukabumi district. The angular instruments used in this study are based on three things: math study, mathematical materials, and the use of ICT with the analysis techniques used are (1) studying all the data gathered, (2) studying the open angular response results (3) describing ICT - supported teaching needs. Based on the results of this research analysis, math learning uses a saintifical approach and a variety of approaches consistent with the material and the characteristics of he student, the study of mathematical materials is desirable when the relative material is easy to understand, and the use of ICT is essential because it can not only accommodate and strengthen the student's imagination in understanding mathematical materials. Thus, teaching that is appropriate and can sustain students' ability in the learning process, which is in the LKS form by providing ict assistance.